Repertório de habilidades sociais e vivência universitária de estudantes com transtorno do espectro autista - Reggi, Maria Eduarda Primo (Universidade Federal de São Carlos, 2025)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by persistent deficits in communication and social interaction, as well as repetitive and restricted behavior patterns. Symptoms can be worsened by late diagnosis and lack of early intervention, impacting social skills essential for the quality of life and inclusion of autistic adults. Higher education is a critical context for students' mental health, and social skills are protective factors against academic adversity and psychological distress, becoming even more relevant for autistic students. This study aimed to identify the social skills repertoire of university students with ASD and to investigate possible correlations with time since diagnosis. Sixty university students from Brazilian institutions (30 with ASD and 30 without a diagnosis) participated in the study and completed a sociodemographic questionnaire and the Social Skills Inventory 2. Descriptive statistical analyses, correlation analyses, and group differences analyses were performed, as well as thematic content analysis. The ASD group presented a significantly lower repertoire of social skills, particularly assertive communication and expressing positive feelings. There was no significant correlation between time since diagnosis and social skills. Greater difficulties were reported in social or academic avoidance, initiating interactions, and participating in groups, with reports of isolation and a lack of belonging. The results reinforce the need for specific interventions that promote belonging and strengthen bonds in the university context, in addition to providing support for public policies and future research on the inclusion and mental health of autistic university students.
Social skills repertoire and university experience of students with autism spectrum disorder
Keywords: Transtorno do Espectro Autista; Autism Spectrum Disorder; Habilidades sociais; Social skills; CIENCIAS HUMANAS::PSICOLOGIA